RETRACTED: Energy security and sustainable development from the standpoint of energy paradigm of Iran - Guzikova Liudmila; Niyetalina Gaukhar; Ahmadi Simin Shahbazi; Israilova Elima; Shmatko Larisa (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001